2013
DOI: 10.5897/jdae12.065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of property rights on agricultural production: The Nigerian experience

Abstract: The study was conducted to examine the effects of property rights and other factors on the outputs of maize, yam and cassava in three zones of Osun State in Nigeria. This study employed a multi-stage sampling technique to select 105 farmers involving growers of maize, yam and cassava in the study area. Data were analyzed with the aid of descriptive statistics, budgetary techniques and a multiple linear regression model. The results of budgetary analysis showed that variable cost was highest in yam production. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
4
5
0
Order By: Relevance
“…There are majorly three types of land tenure systems subscribed to in the study area. These comprise of statutory, customary and informal systems (this is congruent with what was obtainable in other parts of the country [8,11,26]. Table 2 showed that customary land tenure system is the most subscribed in the study area with a mean of 60.1%.…”
Section: Resultssupporting
confidence: 76%
“…There are majorly three types of land tenure systems subscribed to in the study area. These comprise of statutory, customary and informal systems (this is congruent with what was obtainable in other parts of the country [8,11,26]. Table 2 showed that customary land tenure system is the most subscribed in the study area with a mean of 60.1%.…”
Section: Resultssupporting
confidence: 76%
“…There are majorly three types of land tenure systems subscribed to in the study area. These comprise of statutory, customary and informal systems (this is congruent with what was obtainable in other parts of the country (Fabiyi, 2009;Christian, 2009;Akinola and Adeyemo, 2013). Table 2 showed that customary land tenure system is the most subscribed in the study area with a mean of 60.1%.…”
Section: Resultssupporting
confidence: 75%
“…The result indicates that most of the respondents are married, which implies that most respondents have family responsibilities. According to Akinola and Adeyemo (2013), it is expected that married farmers have a greater number of labour for farm work. If primary school completion is taken to be a sound literacy level, the result revealed that approximately 78.3% of the respondents could read or write.…”
Section: Demographic and Socio-economic Characteristics Of The Respon...mentioning
confidence: 99%